PENGELOLAAN AKUT KIDNEY INJURY DISEBABKAN SEPSIS DI ICU - Marisi, Suhud; Suwarman; Maskoen, Tinni (E-Journal Widya Kesehatan dan Lingkungan, 2021)
Acute Kidney Injury (AKI) is a syndrome that consists of several clinical conditions, due to sudden kidney dysfunction. Sepsis and septic shock are the causes of AKI and are known as Sepsis-Associated AKI (SA-AKI) and account for more than 50% of AKI cases in ICU, with a trend towards a poor prognosis. Acute Kidney Injury (AKI) is characterized by a sudden decrease in kidney function over several hours / day, which results in the accumulation of creatinine, urea and other waste products. The main goals of AKI management are to prevent further kidney damage and to keep the patient alive until the kidney function returns to normal. SA-AKI is a condition often faced by patients with sepsis in the ICU. The method used is based on a literature review regarding the reduction in mortality or success in patient management, in the BEST Kidney trial subgroup analysis, the probability of death in hospital was 50% higher in AKI sepsis compared with non-sepsis AKI. The understanding of sepsis and endotoxin that can cause SA-AKI is not fully known, the conclusion is that rapid identification of the incidence of SA-AKI, antibiotics and appropriate fluid therapy are crucial actions in the management of SA-AKI. The availability of organ support modalities such as CRRT in ICU care can help patients with sepsis survive due to frequent kidney organ failure.